Human immunodeficiency virus type 1 detected in all seropositive symptomatic and asymptomatic individuals. - Jackson, J B (1990)
Between February 1987 and October 1988, peripheral mononuclear blood cells (PBMC) from 409 adult individuals antibody positive by Western (immuno-)blot for human immunodeficiency virus type 1 (HIV-1) (56 acquired immunodeficiency syndrome [AIDS] patients, 88 patients with AIDS-related complex, and 265 asymptomatic individuals) were consecutively cultured for HIV-1 or tested for the presence of HIV-1 DNA sequences by a polymerase chain reaction assay (PCR). We isolated HIV-1 or detected HIV-1 DNA sequences from the PBMC of all 409 HIV-1 antibody-positive individuals. None of 131 healthy HIV-1 antibody-negative individuals were HIV-1 culture positive, nor were HIV-1 DNA sequences detected by PCR in the blood specimens of 43 seronegative individuals. In addition, HIV-1 PCR and HIV-1 culture were compared in testing the PBMC of 59 HIV-1 antibody-positive and 20 HIV-1 antibody-negative hemophiliacs. Both methods were found to have sensitivities and specificities of at least 97 and 100%, respectively. In contrast, the sensitivities of serum HIV-1 antigen testing in AIDS patients and asymptomatic seropositive patients were 42 and 17%, respectively. Our ability to directly demonstrate HIV-1 infection in all HIV-1 antibody-positive individuals provides definitive support that HIV-1 antibody positivity is associated with present HIV-1 infection. Moreover, the sensitivities and specificities of PCR and culture for the detection of HIV-1 appear to be equivalent, and both methods are superior to testing for HIV-1 antigen in serum for the direct detection of HIV-1.